Human Resource Management Practices in the Era Of Khulafā’ Aal-Rāshidīn (11-40 AH / 632-661 AD) - Abdul Ghani Azmi, Ilhaamie; Hamzah., Norhayati (Jurnal Usuluddin, 2015)
Quality human capital is significant to every organization due to the fact that it is not only an asset to employer but indeed determining the increase of organizational performance. Human resource management practices in Islamic Civilization aim at selecting and producing quality human capital. These practices have been applied in Islamic history since the early period of Islam especially in the era of Khulafā’ al-Rāshidīn that comprises the caliphate of Abū Bakr al-Ṣiddīq, ‘Umar al-Khattāb, ‘Uthmẓn b. ‘Affān and ‘Alī b. Abi Ṭālib. Hence, this article will elaborate the implementation of human resource management practices i.e. selection and recruitment of workers, training and development as well as salary during the above mentioned period. Human resource management practices that were implemented in the era of Khulafā’ alRāshidīn is certainly a continuous policy of the Prophet Muhammad (p.b.u.h.).